Proceedings of the International Conference on Signal, Networks, Computing, and Systems ICSNCS 2016, Volume 2 - Lobiyal, Daya K.; Mohapatra, Durga Prasad; Nagar, Atulya; Sahoo, Manmath N. (Lecture Notes in Electrical Engineering,, 2016)
The book is a collection of high-quality peer-reviewed research papers presented in the first International Conference on Signal, Networks, Computing, and Systems (ICSNCS 2016) held at Jawaharlal Nehru University, New Delhi, India during February 25-27, 2016. The book is organized in to two volumes and primarily focuses on theory and applications in the broad areas of communication technology, computer science and information security. The book aims to bring together the latest scientific research works of academic scientists, professors, research scholars and students in the areas of signal, networks, computing and systems detailing the practical challenges encountered and the solutions adopted.